2020
DOI: 10.3390/brainsci10100723
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in High-Grade Glioma: A Review

Abstract: High-grade glioma (HGG) is characterized by debilitating neurologic symptoms and poor prognosis. Some of the suffering this disease engenders may be ameliorated through palliative care, which improves quality of life for seriously ill patients by optimizing symptom management and psychosocial support, which can be delivered concurrently with cancer-directed treatments. In this article, we review palliative care needs associated with HGG and identify opportunities for primary and specialty palliative care inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 77 publications
2
17
0
2
Order By: Relevance
“…Existing literature, including four previous reviews on support systems of brain tumour patients, have only focused on palliative care [26,28], interventions [45], telemedicine [46], non-medical therapies [28], and caregivers [28]. The current systematic review examined patient support services in the acute diagnostic period based on qualitative analysis of 14 studies, classified into three support domains: (1) format and level of information provided to patients [14,35,36,[39][40][41][42], (2) ongoing communication with patients [14,15,34,35,38,41,43,44,47] and (3) patient participation in treatment [5,38,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature, including four previous reviews on support systems of brain tumour patients, have only focused on palliative care [26,28], interventions [45], telemedicine [46], non-medical therapies [28], and caregivers [28]. The current systematic review examined patient support services in the acute diagnostic period based on qualitative analysis of 14 studies, classified into three support domains: (1) format and level of information provided to patients [14,35,36,[39][40][41][42], (2) ongoing communication with patients [14,15,34,35,38,41,43,44,47] and (3) patient participation in treatment [5,38,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Research has focused on advanced disease stages [26][27][28], caregivers [28], palliative care [26,28], and nonmedical interventions [28]. The current systematic review is unique in its focus on the psychosocial needs of brain cancer patients at the diagnostic stage, analysing strategies to improve support during this period on the macroand micro-levels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that future studies within the neuro-cognitively impaired patients with dementia should assess the family dynamics and health problems of caregivers, and develop appropriate family-centered interventions that focus on strengthening interfamily support and respite services to alleviate caregiver burden (Liu & Huang, 2018). The value of incorporating a family perspective in neuro-oncological care is recommended (Crooms et al, 2020;Philip et al, 2018), with growing dyadic interventions (Milbury et al, 2019;Ownsworth et al, 2019;Xiao et al, 2018) that acknowledge the neuro-oncological caregivers' valuable support.…”
mentioning
confidence: 99%
“…Therefore, the di culty of primary malignant brain tumor patients of dying in their preferred place may be underestimated, and in other general settings, more patients might not achieve death in their preferred place. Studies have reported that EOL decision-making is often a challenge for primary malignant brain tumor patients [10,15,32]. This is due to the typical symptoms of malignant brain tumor that affect communication from an early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high symptom burden and the fatal illness, the supportive care and/or end-of-life (EOL) care needs of patients with malignant brain tumors may differ from those of patients with other cancers [3][4][5][6]]. Previous studies have reported that patients with primary malignant brain tumors require more support for decisionmaking and physical symptoms than other patients with cancer during EOL care due to cognitive/functional impairment [7][8][9][10]. However, the QOL at EOL, more speci cally, the quality of dying, of patients with malignant brain tumors has not been su ciently investigated.…”
Section: Introductionmentioning
confidence: 99%